Tribulationis Tempore : The Latin Church of Jerusalem in the Palestine War and Its Aftermath, 1946-56 - Rioli, Maria Chiara (Open Jerusalem, 2020)
The history of Palestine War does not only concern military history. It also involves social, humanitarian and religious history, as in the case of Jerusalem's Roman Catholic diocese. Tribulationis Tempore offers a complex narrative on this church, commonly portrayed as monolithically aligned with anti-Zionist and anti-Muslim positions during the "long 1948". Making use of largely unpublished archives in the Middle East, Europe and the United States, including the recently released Pius XII papers, Maria Chiara Rioli depicts a church engaged in multiple and sometimes contradictory pastoral initiatives amid battles, relief missions for Palestinian refugees, theological reflections on Jewish converts to Catholicism, political relations with the Israeli and Jordanian authorities and liturgical responses to this fluid and uncertain scenario.